2015
DOI: 10.1590/1678-7153.201528413
|View full text |Cite
|
Sign up to set email alerts
|

Hot Flushes and Night Sweats in Midlife: Why do Some Women Have Them and Others do Not?

Abstract: This study investigated what predicts the occurrence of hot fl ushes (HF) and night sweats (NS). A community sample of 992 women (42-60 years) answered a questionnaire to collect socio-demographic, health and menopause-related, as well as lifestyle information. Depressive mood and stress, as well as HF and NS (in terms of presence, frequency and intensity), were also assessed. Structural equation modelling was used to build a structural model to predict the occurrence of both vasomotor symptoms. Results: Stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Factors associated with HFNS in the general population include lower levels of education [ 21 , 22 ], African American race [ 23 , 24 ], younger age [ 25 ] and being without a partner [ 26 , 27 ]. The cognitive model of HFNS explains how the perception, attribution and appraisal of menopausal symptoms are influenced by cognitive factors, beliefs and mood [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Factors associated with HFNS in the general population include lower levels of education [ 21 , 22 ], African American race [ 23 , 24 ], younger age [ 25 ] and being without a partner [ 26 , 27 ]. The cognitive model of HFNS explains how the perception, attribution and appraisal of menopausal symptoms are influenced by cognitive factors, beliefs and mood [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…9; Issue: 11; November 2022 findings are consistent with the findings of the study done in Portugal among 992 women aged 42-60 years which revealed that women with experience of hot flushes had significantly higher levels of stress. [18] Similarly, Study findings of Pakistan among 150 women aged 40-60 years showed that fatigue was significantly positively associated with stress among perimenopausal women. [4] Likewise, study findings of India among 75 (postmenopausal and perimenopausal women with symptoms and without symptoms-25 in each group) women showed that there was a significant difference in stress level among three groups with anxiety, vasomotor symptoms, memory disturbances, and sleep disturbances with p-value < 0.001 for all symptoms.…”
Section: Relationship Between Stress and Coping Among Perimenopausal ...mentioning
confidence: 99%